EFFECTIVENESS OF LOCAL FOOD–BASED NUTRITION EDUCATION AND IRON SUPPLEMENTATION ON HEMOGLOBIN LEVELS IN SECOND-TRIMESTER PREGNANT WOMEN - Dianita Widya Gandhi; Gunarmi; Toto Sudargo; Nurhayati; Juda Julia Kristiarini (International Archives of Medical Sciences and Public Health, 2026)
Anemia affects 40.0% of pregnant women in Taliabu Island Regency, North Maluku—a severe public health problem by WHO classification. This study evaluated the effectiveness of local food-based nutrition education combined with iron supplementation on hemoglobin levels in second-trimester pregnant women. A quasi-experimental pretest posttest control group design was conducted from October to December 2025. Forty-four pregnant women (13–28 weeks gestation) were recruited by purposive sampling and allocated by facility to an intervention group (n = 22) or control group (n = 22). Over eight weeks, the intervention group received four biweekly nutrition education sessions using the P-Process framework, weekly locally sourced iron-rich foods, and daily iron-folic acid supplementation (60 mg elemental iron, 400 mcg folic acid); controls received supplementation only. Hemoglobin was measured by HemoCue hemoglobinometry at baseline and endpoint, and analyzed using the Wilcoxon Signed Rank and Mann-Whitney U tests. The intervention group showed significant within-group hemoglobin improvement (Z = -4.110, p < 0.001) and higher endpoint hemoglobin than controls (Z = -5.691, p < 0.001). Tablet compliance was also higher (Z = -6.032, p < 0.001), though knowledge, attitude, and practice scores did not differ (p = 1.000). Local food-based nutrition education integrated with iron supplementation is more effective than supplementation alone and is recommended for scale-up in comparable remote, resource-constrained settings.